Des Romantiques aux écocritiques. Le Romantisme comme militantisme pour écrire la terre en danger - Françoise Besson (Caliban: French Journal of English Studies)
Romantic poets were precursors leading people toward awareness and toward a questioning about humans' presence to the world. They used vision as a "fighting weapon" as Deleuze says. They found in nature the inspiration of a poetic, and also philosophical and political revolution that was to make the world progress in the centuries to come. Ecocritics work in their wake to "try to understand the human relations with the nonhuman world through texts," as Scott Slovic defines the concept. Travelling becomes both an opening to the world and to the writer's own inner world and it appears as the sign of engagement. The close link between Romantic poets, environmental writers and ecocritics perhaps dwells on their common use of the eyes as both an instrument of perception and of engagement.